2017
DOI: 10.1093/trstmh/trx047
|View full text |Cite
|
Sign up to set email alerts
|

Should we be treating animal schistosomiasis in Africa? The need for a One Health economic evaluation of schistosomiasis control in people and their livestock

Abstract: A One Health economic perspective allows informed decisions to be made regarding control priorities and/or implementation strategies for infectious diseases. Schistosomiasis is a major and highly resilient disease of both humans and livestock. The zoonotic component of transmission in sub-Saharan Africa appears to be more significant than previously assumed, and may thereby affect the recently revised WHO vision to eliminate schistosomiasis as a public health problem by 2025. Moreover, animal schistosomiasis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 24 publications
(31 reference statements)
0
85
0
1
Order By: Relevance
“…While some of the authors consider relatively recent infectious disease emergence, such as Middle East Respiratory Syndrome, 3 others examine longer-standing public health risks. These include schistosomiasis, 1,4 which continues to exact a large burden in sub-Saharan Africa despite affordable and effective prophylaxis and treatment options, in part because infected livestock are kept near human water sources. Still other contributions examine global efforts to combat emerging antimicrobial resistance (AMR).…”
mentioning
confidence: 99%
“…While some of the authors consider relatively recent infectious disease emergence, such as Middle East Respiratory Syndrome, 3 others examine longer-standing public health risks. These include schistosomiasis, 1,4 which continues to exact a large burden in sub-Saharan Africa despite affordable and effective prophylaxis and treatment options, in part because infected livestock are kept near human water sources. Still other contributions examine global efforts to combat emerging antimicrobial resistance (AMR).…”
mentioning
confidence: 99%
“…The impact of zoonotic transmission to human infection differs by species and this influences the impact of different interventions. Some studies investigating S. japonicum included targeting the zoonotic reservoir (Table 1) but further work is needed to investigate the costs and benefits of applying a one health approach across a range of settings 133 .…”
Section: Evaluation Of Alternative Interventions and Strategiesmentioning
confidence: 99%
“…Other than some proteomic analyses of S. bovis and the S. bovis -host interface, aimed at identifying potential new vaccine and drug targets [ 69 ], it is surprising that no recent research has been reported in the development and testing of different vaccines targeting schistosomiasis infections caused by S. bovis and S. mattheei in livestock, despite the early encouraging successes. This may be somewhat short-sighted as it has been recently argued that animal schistosomiasis likely causes a considerable drain, both directly and indirectly, on the local economy of many poor communities in sub-Saharan Africa [ 70 ]. Further, the zoonotic component of schistosomiasis transmission in Africa appears to be far more significant and important than previously thought [ 6 ], and this may impact on the current WHO vision to eliminate schistosomiasis as a public health issue by 2025.…”
Section: Challenges and Opportunities For The Futurementioning
confidence: 99%